PERAN AVIATION SECURITY DALAM RANGKA MENANGKAL UPAYA KEJAHATAN PENERBANGAN (STUDI PUSTAKA DI MASKAPAI PENERBANGAN) - Setiadi, Bekti (STP AVIASI, 2018)
The role of Aviation Security in maintaining, observing, researching and inspecting passengers, passenger's belongings is an obligation in the field of aviation. Aviation Security in performing the work either in the airport environment or in the airline is carried out according to the expertise required by the Directorate General of Civil Aviation must have a tiered license ranging from Basic Aviation Security to Senior Aviation Security. Therefore, library studies on aviation security is expected to provide benefits to the aviation world, especially in terms of security and flight safety.